2005
DOI: 10.1021/jf0505731
|View full text |Cite
|
Sign up to set email alerts
|

Development of Taxon-Specific Sequences of Common Wheat for the Detection of Genetically Modified Wheat

Abstract: Qualitative and quantitative Polymerase Chain Reaction (PCR) systems aimed at the specific detection and quantification of common wheat DNA are described. Many countries have issued regulations to label foods that include genetically modified organisms (GMOs). PCR technology is widely recognized as a reliable and useful technique for the qualitative and quantitative detection of GMOs. Detection methods are needed to amplify a target GM gene, and the amplified results should be compared with those of the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…Although detection methods of wheat 3,5) in food by PCR have been developed, it has not been possible to distinguish different wheat species. In this study, qualitative PCR methods to distinguish wheat species with two primer pairs were developed.…”
Section: Resultsmentioning
confidence: 99%
“…Although detection methods of wheat 3,5) in food by PCR have been developed, it has not been possible to distinguish different wheat species. In this study, qualitative PCR methods to distinguish wheat species with two primer pairs were developed.…”
Section: Resultsmentioning
confidence: 99%
“…A DNA sequence with a single or stable low copy number should yield similar Ct values among varieties. We previously concluded that common wheat genomic DNAs have either single or double copies of the Wx012 region 21 . To estimate the copy number of the PRP region in the common wheat genome, we performed quantitative analyses of the PRP and Wx012 regions.…”
Section: Copy Number Of the Prp Regionmentioning
confidence: 99%
“…We calculated and compared the copy number of the Wx012 region and that of the PRP region. In this experiment, durum wheat was not included because the Wx012 system does not work on durum wheat 21 .…”
Section: Copy Number Of the Prp Regionmentioning
confidence: 99%
“…This strategy was then described in a guidance document published on the EURL-GMFF website (European Union Reference Laboratory for GM Food and Feed 2013a), together with a comprehensive review and related bioinformatics analysis on all available relevant literature on taxon-specific real-time PCR systems for the identification of T. aestivum (European Union Reference Laboratory for GM Food and Feed 2013b). The results of the study suggested that the method described by Matsuoka et al (2012), targeting ssII-D gene coding for starch synthase, and the one described by Iida et al (2005), targeting waxy-D1 gene, coding for granule-bound starch synthase, may represent good candidates to specifically identify common wheat even in complex food samples. With regard to the latter method, what was reported in the above-mentioned EURL-GMFF guidelines had to be carefully considered, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the latter method, what was reported in the above-mentioned EURL-GMFF guidelines had to be carefully considered, i.e. Baccording to in silico analyses conducted by the EURL GMFF, the primer sequences described in Iida et al 2005 are not correct. The primers (Wx012F/Wx012R) and probe (Wx-Taq 1) sequences reported by the same authors in the following article: BImai et al (2012), Food Hyg.…”
Section: Introductionmentioning
confidence: 99%